2006
DOI: 10.3132/dvdr.2006.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for stroke in type 2 diabetes mellitus

Abstract: Stroke is a serious complication of diabetes but the risk factors for stroke in these patients are not fully defined. The aim of this retrospective study was to investigate the risk factors for stroke in patients with type 2 diabetes mellitus (T2DM). The group comprised 208 patients with T2DM, and the mean duration of followup was seven years (range 4-11 years). The incidence of stroke was investigated according to lymphocyte proliferation in response to insulin.Using cimetidine to inhibit cells with histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…High levels of hs-CRP and NO and chronic inflammation are associated with insulin resistance and vascular diseases (Doi et al 2005;Martyn et al 2008;Asfandiyarova et al 2006). Bradykinin acts as a vascular dilator and its expression is down-regulated by angiotensin-converting enzyme (ACE).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of hs-CRP and NO and chronic inflammation are associated with insulin resistance and vascular diseases (Doi et al 2005;Martyn et al 2008;Asfandiyarova et al 2006). Bradykinin acts as a vascular dilator and its expression is down-regulated by angiotensin-converting enzyme (ACE).…”
Section: Discussionmentioning
confidence: 99%
“…When considering age-adjusted incidence rates, type-2 diabetic patients are two- to five times as likely to suffer cerebral vascular disease or stroke compared with non-diabetic patients, a disparity that is seen in multiple racial/geographic groups [2][6] and may result from abnormal cerebral artery tissue function. Interestingly, the incidence of stroke in type-2 diabetic patients is not associated with the duration of disease, smoking, fasting blood glucose, total cholesterol, lipoprotein concentrations, or hypertension [3], [4], [7]. Cerebral blood flow disturbances, impaired cerebral vascular reactivity, transient ischemic attacks and oxidative damage of cerebral vessels have been found in both type-2 diabetic patients [3] and experimental models [8][10] that could account for the higher incidence of diabetes-related stroke events [1]–[7]; however, the molecular mechanisms involved in cerebral artery dysfunction are not completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with disturbances of carbohydrate metabolism the course of stroke is worse, the period of rehabilitation is longer and the mortality rate is higher (27). Some systematic overview shows that in patients with no history of diabetes who have an ischemic stroke, even moderately elevated glucose levels are associated with both a 3-fold higher risk of short-term mortality and an increased risk of poor functional recovery compared with lower glucose levels.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that high blood pressure is an independent risk factor for stroke in diabetic patients (9,10) .In some studies concerning the joint prognostic effect of hypertension and type 2 diabetes on stroke risk in the general population, it is not well known whether the increasing risk of stroke comes from the effect of hypertension or type 2 diabetes alone or from the combined effect of both hypertension and type 2 diabetes (11,12) .It is suggested that one of the risk factors for stroke in patients with T2DM is high activity of cells with histamine receptors and prostaglandin-synthesising cells. These cells suppress cell-mediated immunity to insulin and may have a role in promoting the development of insulin resistance (13) .…”
Section: Risk Factorsmentioning
confidence: 99%